Transradial versus transfemoral access for embolization of intracranial aneurysms with the Woven EndoBridge device: a propensity score-matched study - Dibas, Mahmoud; Adeeb, Nimer; Diestro, Jose Danilo Bengzon; Cuellar, Hugo H.; Sweid, Ahmad; Lay, Sovann V.; Guenego, Adrien; Aslan, Assala; Renieri, Leonardo; Sundararajan, Sri Hari; Saliou, Guillaume; Möhlenbruch, Markus Alfred; et al. (Journal of neurosurgery, 2022)
OBJECTIVE Transradial access (TRA) is commonly utilized in neurointerventional procedures. This study compared the technical and clinical outcomes of the use of TRA versus those of transfemoral access (TFA) for intracranial aneurysm embolization with the Woven EndoBridge (WEB) device. METHODS This is a secondary analysis of the Worldwide WEB Consortium, which comprises multicenter data related to adult patients with intracranial aneurysms who were managed with the WEB device. These aneurysms were categorized into two groups: those who were treated with TRA or TFA. Patient and aneurysm characteristics and technical and clinical outcomes were compared between groups. Propensity score matching (PSM) was used to match groups according to the following baseline characteristics: age, sex, subarachnoid hemorrhage, aneurysm location, bifurcation aneurysm, aneurysm with incorporated branch, neck width, aspect ratio, dome width, and elapsed time since the last follow-up imaging evaluation. RESULTS This study included 682 intracranial aneurysms (median [interquartile range] age 61.3 [53.0-68.0] years), of which 561 were treated with TFA and 121 with TRA. PSM resulted in 65 matched pairs. After PSM, both groups had similar characteristics, angiographic and functional outcomes, and rates of retreatment, thromboembolic and hemorrhagic complications, and death. TFA was associated with longer procedure length (median 96.5 minutes vs 72.0 minutes, p = 0.006) and fluoroscopy time (28.2 minutes vs 24.8 minutes, p = 0.037) as compared with TRA. On the other hand, deployment issues were more common in those treated with TRA, but none resulted in permanent complications. CONCLUSIONS TRA has comparable outcomes, with shorter procedure and fluoroscopy time, to TFA for aneurysm embolization with the WEB device.